Perceptual organization and visual awareness: the case of amodal completion - Kimchi, Ruth; Devyatko, Dina; Sabary, Shahar (Frontiers in Psychology, 2023)
We investigated the involvement of visual awareness in amodal completion, and specifically, whether visual awareness plays a differential role in local versus global completion, using a primed shape discrimination paradigm and the color-opponent flicker technique to render the prime invisible. In four experiments, participants were presented with a partly occluded prime followed by a clearly visible target. In all primes, the local completion (based on good continuation) and the global completion (based on object symmetry) diverged into different shapes. The target corresponded to the shape that could arise from a local or a global completion of the prime. For each experiment with an invisible prime we conducted a version with a visible prime. Our results suggest that local completion, but not global completion, of a partly occluded shape can take place in the absence of visual awareness, but apparently only when the visible occluded shape generates a single, local completion. No completion, either local or global, appears to take place in the absence of visual awareness when the visible occluded shape generates multiple completions. The implications of these results to the differential role of visual awareness in local and global completions and to the relationship between multiple completions and unconscious amodal completions are discussed.